CASE STUDY OF KERINCI TYPICAL BATIK AT THE INCOANG.GNCE BATIK SANGGAR SUNGAI PENUH - Fina Herdyanti; Puji Hujria Suci (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Batik in Indonesia was acknowledgen by unesco in 2009 as an intangible cultural treasure, and each region has batik with different characteristics and characteristics. One of the batik producing areas is in Kerinci, Sungai Full City, specifically at the Incoang.gnce Batik Studio which was founded in 2016. The method for creating batik in this studio uses the stamped batik technique and creates batik with the characteristics of Kerinci, Sungai Full City. The study’s objective is to characterize the background to the establishment of the Incoang.gnce batik studio, describe the form of batik motifs and the process of making typical Kerinci batik at the Incoang.gnce Batik Studio. The research method applies a qualitative descriptive method, the type of data used is primary and secondary data. Data collection techniques use observation, interviews and documentation techniques. Data analysis techniques with data reduction steps, data exposure and conclusions. To test the validity of the data, triangulation was carried out with the owner of the Incoang.gnce Batik Studio. The results of this research concluded that the Incoang.gnce batik studio was founded in 2016 based on batik training from the industry department, the batik motifs were sourced from what was in Kerinci, the river city full of culture and then typical Kerinci batik was created at the Incoang Gnce batik studio. Examples of motifs include the Karamantang motif, Umoh Lahaek motif, Jangkoi motif, Manyang motif, Kawoa motif, Incung script motif. The batik making process at the Incoang.gnce batik studio uses the stamped batik technique, starting from the stamping process, the coloring process, the embossing process, the dyeing process, and the lorot process. The tools used in making batik include stamping tables, stamping canting, frying pans and stoves. Materials used in batik are wax, dye, soda ash and water glass.